2018
DOI: 10.3892/mmr.2018.9303
|View full text |Cite
|
Sign up to set email alerts
|

The bimodal role of matrix metalloproteinases and their inhibitors in etiology and pathogenesis of endometriosis (Review)

Abstract: Aberrant regulation of matrix metalloproteinases (MMPs) may be the primary cause of endometrial lesion formation in a group of predisposed women. Prospect for the genuine origin of endometriosis is ongoing, since retrograde menstruation leads to presence of endometrial debris in peritoneal cavity of many women, which do not experience endometriosis. Tissue remodeling is regulated precisely by a balance of MMPs and their inhibitors. Interplay between factors enhancing and suppressing matrix turnover is crucial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
64
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 109 publications
(116 reference statements)
2
64
0
5
Order By: Relevance
“…In light of these information, here we demonstrate that different MMPs are expressed at different levels in healthy and pathological tissues, in accordance with data reported by most of the studies focused on this disease [24,25,27].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In light of these information, here we demonstrate that different MMPs are expressed at different levels in healthy and pathological tissues, in accordance with data reported by most of the studies focused on this disease [24,25,27].…”
Section: Discussionsupporting
confidence: 92%
“…Another interesting finding of the present work is the proven increase in MMP2 expression in OMA, that confirms data reporting higher activity of MMP2 in ectopic lesions in comparison to uterine endometrium [24,30,31]. Altered expression of gelatinases has been correlated to the metastatic state; therefore, these enzymes can influence the ability of cells to invade and metastasize due to their aptitude to degrade the basement membrane [32].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although recent studies have demonstrated that endometrial organoid cultures can be used to achieve the complexity of organ structures to a considerable degree through cellular self-assembly and can be used as preclinical models to study the physiology and pathology of human endometrium [17][18][19][20][21][22][23][24], these models do not fully recapitulate the regulatory mechanisms of endometrium in vivo. Herein with the use of full thickness endometrial tissue slice cultures we developed a unique model that dramatically enhances endometrial tissue viability and recapitulates the zone-specific changes seen in normal physiological conditions of endometrium [52][53][54]. It has been reported that the pattern of expression and localization of signaling molecules in cells at various zones of endometrium vary throughout the menstrual cycle but parallel to the cyclical changes in the endometrium; and aberrations in the expression pattern are associated with pathological conditions such as endometriosis [55][56][57].…”
Section: Induction Of Glandular Remodeling and Decidualization In Endmentioning
confidence: 99%